Distal overactivation of gastrocnemius medialis in persistent plantarflexion weakness following Achilles tendon repair. (February 2023) - De la Fuente, Carlos; Martinez-Valdes, Eduardo; da Rocha, Emmanuel S.; Geremia, Jeam M.; Vaz, Marco A.; Carpes, Felipe P.
Abstract: Structural alterations of the triceps surae and Achilles tendon (AT) can promote plantarflexion weakness one-year following an AT repair, influencing the activation strategies of the Gastrocnemius Medialis (GM) muscle. However, this is yet to be demonstrated. We aimed to determine whether patients with plantar flexion weakness one-year after AT repair show altered GM spatial activation. In this cross-sectional and case-control study, ten middle-aged men (age 34 ± 7 years old, and 12.9 ± 1.1 months post-surgery) with a high AT total rupture score who attended conventional physiotherapy for six months after surgery, and ten healthy control men (age 28 ± 9 years old), performed maximal and submaximal (40, 60 and 90%) voluntary isometric plantarflexion contractions on a dynamometer. The peak plantar flexor torque was determined by isokinetic dynamometry and the GM neuromuscular activation was measured with a linear surface-electromyography (EMG) array. Overall EMG activation (averaged channels) increased when the muscle contraction levels increased for both groups. EMG spatial analysis in AT repaired group showed an increased activation located distally at 85–99%, 75–97%, and 79–97% of the electrode array length for 40%, 60%, and 90% of the maximal voluntary isometric contractions, respectively. In conclusion, patients with persistent plantar flexion weakness after AT rupture showed higher distal overactivation in GM.